New records of some phytoplankton for Bangladesh: Class - Chlorophyceae (Bangladesh Journal of Plant Taxonomy, 2020)
The paper records 6 species of phytoplankton under the class Chlorophyceae namely, Pteromonas golenkiniana Pascher belonging to Family Phacotaceae; Pediastrum biradiatum var. biradiatum Meyen.belonging to Family Hydrodictyaceae; Scenedesmus alternas var. indicus Hortob. and Scenedesmus quadricauda var. inermis Playfair belonging to Family Scenedesmaceae ; Teilingia excavata (Rafls) Bourelly and Cosmarium vexatum W. West var. vexatum W. West belonging to Family Desmidaceae from Sylhet Division of Bangladesh which are all new records for Bangladesh.Bangladesh J. Plant Taxon. 27(1): 79-83, 2020 (June)